Effects of moderate abundance changes on the atmospheric structure and colours of Mira variables: research note - Scholz, Michael; Ireland, Michael J.; Wood, Peter R. (Astronomy and astrophysics, 2014)
Aims. We study the effects of moderate deviations from solar abundances upon the atmospheric structure and colours of typical Mira variables.Methods. We present two model series of dynamical opacity-sampling models of Mira variables which have (1) 1/3 solar metallicity; and (2) “mild” S-type C/O abundance ratio ([C/O] = 0.9) with typical Zr enhancement (solar +1.0). These series are compared to a previously studied solar-abundance series which has similar fundamental parameters (mass, luminosity, period, radius) that are close to those of o Cet.Results. Both series show noticeable effects of abundance upon stratifications and infrared colours but cycle-to-cycle differences mask these effects at most pulsation phases, with the exception of a narrow-water-filter colour near minimum phase.